Features of raisins grape quality according to the drying process method used - Espíndola, Rodrigo Sebastián; Gutierrez, Aida; Suero, Eduardo (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
The province of San Juan produces the 90% of grape raisins in Argentina. The main drying method uses solar energy on drying yards built with gravel. In the recent years, others drying methods have appeared: dry on vine, drying on structures or drying on plastics tarps. The raisins made by different method have different features about color, appearance, flavor, incrustations, mold or other kind of quality problems. This study assessed the quality characters in grape raisins drying by gravel yard, plastic tarps, metal structures and drying on vine. Up to 32 raisin samples were evaluated about physic features. Also organoleptic evaluation and ochratoxin A analysis were made. The data were process by SPSS 15.0 software. Descriptive statistic, ANOVA and cluster analysis were calculated. The results indicated the main problems were raisins out of range, discoloration, out of regular form, irregular wrinkle, crystallization, capstems, damage and spots. The method with the most sugar crystallization and caramelization process was drying by gravel yard. Plastic drying method had the most amount of incrustations or strange materials. Dry on vine raisins do not show any sign of mold or insects. Most percentage of substandard grade are found in plastic drying method. A cluster analysis showed gravel and plastic drying method are closer each other and dry on vine is similar to structure drying method. Gravel method have the most ochratoxin A content. Dry on vine and structure drying method are both the best option for a good raisin quality made on a farm.